Regional development problems of small and medium-sized enterprises in Latvia - Lace, Natalja; Sundukova, Zoja (Vysoké učení technické v Brně, Fakulta podnikatelská, 2007)
Despite the achievements attained in recent years in the economic development of Latvia, until now Latvia’s regions demonstrate uneven development, which negatively impacts the development of small business. The development of the regional innovation environment will contribute to the enhancement of competitiveness of regional economies.
Keywords: Regional development; small and medium-sized enterprises; innovation environment